Komposisi Gulma Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) Sebelum dan Setelah Dilakukan Pengendalian Secara Mekanik dan Kimia - Ratna, Yuni; Pebrianti, Herni Dwinta; Swari, Elly Indra; Muryunika, Rince; Pardosi, Juan Rizki (Universitas Batanghari, 2025)
The presence of weeds in oil palm plantations can reduce fresh fruit bunch production by up to 80%. The applied weed control techniques affect subsequent weed composition. The purpose of this study was to assess the weed composition in oil palm plantations before and after mechanical and chemical weed control. The study was conducted on immature oil palm plantations (TBM) covering an area of approximately 1 ha. Weed vegetation analysis used the quadrat method with a sample plot size of 20 m2 and a sub-sample plot size of 1 m2. The number of sample plots was 9 with 18 sub-sample plots each in the dead stile and disc. The variables observed consisted of the number of weed species, the summed dominance ratio (SDR), and the level of weed distribution. The results showed a shift in the number of weed species before and after mechanical control in the dead stile and chemical control in the disc. There were 34 weed species in the dead stile before cutting and 30 weed species after cutting, while in the disc there were 15 weed species before herbicide application and 10 weed species after herbicide application. There was no shift in weed species with high SDR before and after cutting in the dead stile, while there was a shift in weed species before and after herbicide application in the disc. Weed species with high distribution levels in the dead stile were the same before and after cutting, while in the disc there was a shift in weed species before and after herbicide application. The weed vegetation community was relatively homogeneous before and after cutting and herbicide application.